Big Five personality relationships with general intelligence and specific Cattell-Horn-Carroll factors of intelligence. (1st September 2018) - Osmon, David C.; Santos, Octavio; Kazakov, Dmitriy; Kassel, Michelle T.; Mano, Quintino R.; Morth, Ashten
Abstract: Objective: Though relationships among Big Five personality traits and general intelligence have been found consistently, less is known of how personality traits relate to specific factors of intelligence. The present study examined relationships between Big Five personality traits on the NEO Personality Inventory-Revised (NEO-PI-R; Costa & McCrae, 1992) and g -residualized scores of the seven factors of the Cattell-Horn-Carroll (CHC) model on the Woodcock-Johnson-III (WJ-III; Mather & Woodcock, 2001). Method: College students referred to a learning disorders clinic were assessed with a comprehensive neuropsychological battery that involved cognitive, achievement, and personality testing. The sample was culled for failure on a sensitive effort measure (Word Memory Test; Green, 2003), leaving 140 participants. Results: Openness (O) accounted for significant variance in all seven WJ-III IQ factors with the O-crystallized intelligence (G c ) relationship being strongest and all other personality-IQ relationships being small. However, using residualized scores to remove common intellectual variance showed that Openness related only to G c while Extraversion related to both processing speed and G c . Conclusions: The role that personality plays in the specific aspects of CHC factors of intellectual test performance is discussed in the context of learning difficulties in college students. Highlights: Openness and Conscientiousness are most related to general intelligence ( g ). Big Five variables account for little variance in specific factors of intelligence. Openness is important when interpreting general intellectual performance.